The Paleo-Indian Entry into South America According to Mitogenomes. (31st October 2017) - Brandini, Stefania; Bergamaschi, Paola; Cerna, Marco Fernando; Gandini, Francesca; Bastaroli, Francesca; Bertolini, Emilie; Cereda, Cristina; Ferretti, Luca; Gómez-Carballa, Alberto; Battaglia, Vincenza; Salas, Antonio; Semino, Ornella; et al.
Abstract: Recent and compelling archaeological evidence attests to human presence ∼14.5 ka at multiple sites in South America and a very early exploitation of extreme high-altitude Andean environments. Considering that, according to genetic evidence, human entry into North America from Beringia most likely occurred ∼16 ka, these archeological findings would imply an extremely rapid spread along the double continent. To shed light on this issue from a genetic perspective, we first completely sequenced 217 novel modern mitogenomes of Native American ancestry from the northwestern area of South America (Ecuador and Peru); we then evaluated them phylogenetically together with other available mitogenomes (430 samples, both modern and ancient) from the same geographic area and, finally, with all closely related mitogenomes from the entire double continent. We detected a large number ( N = 48) of novel subhaplogroups, often branching into further subclades, belonging to two classes: those that arose in South America early after its peopling and those that instead originated in North or Central America and reached South America with the first settlers. Coalescence age estimates for these subhaplogroups provide time boundaries indicating that early Paleo-Indians probably moved from North America to the area corresponding to modern Ecuador and Peru over the short time frame of ∼1.5 ka comprised between 16.0 and 14.6 ka.